PENINGKATAN MOTIVASI BERPRESTASI DAN HASIL BELAJAR SISWA PADA TEMA TEMPAT UMUM MELALUI METODE ULAR BERUNTUN - Sutrisno . (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2018)
This study aims to improve achievement motivation and student learning outcomes by using snake streak on the theme of public places third grade SDN 4 Ngraho the first semesterof the school year 2015/2016. This research is a class act consisting of two cycles of the fourphases: planning, action, observation, and reflection. Instruments used in obtaining the data isin the form of tests, observations and achievement motivation questionnaire. Learning is doneby using the syllabus, lesson plan, teaching materials and worksheets. During the study,observation skills processes, activities, and student learning at the end of learning is done byusing a test to determine learning outcomes siswa.Hasil research shows that the hair testresults show improvement. Pre cycle of 57 to 66, in the second cycle, increased to 87, presikulus learning completeness reached 35% in cycle 1 reached 70.5%, in the second cycleincreased to 100%. The results of the questionnaires has increased from cycle 1 to cycle 2,from 78% in both categories increased to 96% with very good category. Based on theseresults it can be concluded that by using the method of successive snakes can increaseachievement motivation and student learning outcomes.Keywords: Achievement Motivation, Learning Outcomes, Public Places, Methods SnakeÂ Burst